Role of Progranulin and its Implication in Knee Osteoarthritis among Iraqi Patients - Shahad Adil Abd Al-Ghafoor, Hind Shakir Ahmed (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Osteoarthritis is a complicated, chronic disorder of cartilage and bone, associated with homeostasis of bio-elements. The current study aims to assess the role of serum progranulin levels among Iraqi patients with knee osteoarthritis. Patients and Methods: The study encompassed 50 patients aged 52.50 ± 3.12 years (25 males and 25 females), admitted to the at the Baghdad Medical City through the period from November 2021 to March 2022. All individuals were identified by physicians in a Rheumatology and Rehabilitation Outpatient Clinic and the clinical data was collected along with the assessment of biochemical parameters. Fasting serum glucose, lipid profile, calcium, magnesium, alkaline phosphatase, vitamin D3, and progranulin levels were determined. Results: All patients in this study had higher levels of serum glucose and dyslipidemia with significant increases (p < 0.05) in alkaline phosphatase and progranulin levels and considerable reduced (p < 0.05) in serum calcium, magnesium, and vitamin D3 as compared to healthy group. Additionally, hypovitaminosis D were appeared in all patients and progranulin levels were (56.30±8.50 ng/mL) vs. (40.45 ± 8.90 ng/mL) in control group with OR and CI= 1.54 (0.97-2.58). Conclusions: Inflammation has an integral role in the pathogenesis of osteoarthritis. Serum vitamin D3 level is considerably low in patients with knee osteoarthritis paralleled to healthy individuals. However, this study demonstrates increased progranulin levels in knee osteoarthritis patients and associates with vitamin D level, disease activity, and inflammation among those patients.